Co-creating scholarship through collaborative writing in health professions education: AMEE Guide No. 143. (3rd April 2022) - Ramani, Subha; McKimm, Judy; Forrest, Kirsty; Hays, Richard; Bishop, Jo; Thampy, Harish; Findyartini, Ardi; Nadarajah, Vishna Devi; Kusurkar, Rashmi; Wilson, Keith; Filipe, Helena; Kachur, Elizabeth
Abstract: This AMEE guide provides a robust framework and practical strategies for health professions educators to enhance their writing skills and engage in successful scholarship within a collaborative writing team. Whether scholarly output involves peer-reviewed articles, book chapters, blogs and online posts, online educational resources, collaborative writing requires more than the usual core writing skills, it requires teamwork, leadership and followership, negotiation, and conflict resolution, mentoring and more. Whilst educators can attend workshops or courses to enhance their writing skills, there may be fewer opportunities to join a community of scholars and engage in successful collaborative writing. There is very little guidance on how to find, join, position oneself and contribute to a writing group. Once individuals join a group, further questions arise as to how to contribute, when and whom to ask for help, whether their contribution is significant, and how to move from the periphery to the centre of the group. The most important question of all is how to translate disparate ideas into a shared key message and articulate it clearly. In this guide, we describe the value of working within a collaborative writing group; reflect on principles that anchor the concept of writing as a team and guide team behaviours; suggest explicit strategies to overcome challenges and promote successful writing that contributes to and advances the field; and review challenges to starting, maintaining, and completing writing tasks. We approach writing through three lenses: that of the individual writer, the writing team, and the scholarly product, the ultimate goal being meaningful contributions to the field of Health Professions Education.